2017
DOI: 10.1038/mp.2017.18
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural and functional signatures of impulsive–compulsive behaviours in Parkinson’s disease

Abstract: This study assessed brain structural and functional alterations in patients with Parkinson's disease and impulsive-compulsive behaviours (PD-ICB) compared with controls and PD no-ICB cases. Eighty-five PD patients (35 PD-ICB) and 50 controls were recruited. All subjects underwent three-dimensional T1-weighted, diffusion tensor (DT), and resting state functional magnetic resonance imaging (RS fMRI). We assessed cortical thickness with surface-based morphometry, subcortical volumes using FIRST, DT MRI metrics us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 50 publications
4
53
0
Order By: Relevance
“…Our findings emphasize that impairments to self‐regulation are a key deficiency in the ICB population. While self‐report measures of impulsivity often have only modest to moderate associations with task‐based measures of cognitive functioning and impulsivity, 6,61,77 many PD patients are indeed aware of alterations in cognitive functioning and behavioral changes 78 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings emphasize that impairments to self‐regulation are a key deficiency in the ICB population. While self‐report measures of impulsivity often have only modest to moderate associations with task‐based measures of cognitive functioning and impulsivity, 6,61,77 many PD patients are indeed aware of alterations in cognitive functioning and behavioral changes 78 …”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of PD patients to impulse control behaviors might be related to a pre‐existing biological predisposition or might occur as a result of dopaminergic medications modulating the neurobiology of PD . Several animal and human studies suggest that these 2 factors may synergistically act on the risk of developing ICD in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, patients with PD and ICD seem to present a novelty‐seeking personality, an inclination for risk‐taking behaviors with impaired decision‐making, and motor inhibition . Evidence from previous metabolic, functional, and morphometric imaging studies has consistently demonstrated dysfunction within the meso‐cortico‐limbic‐striatal circuit in patients with PD and ICD, involving both cortical and subcortical areas engaged in the reward system. However, these studies were performed in patients with PD under dopaminergic treatment and with a present history of impulse control behaviors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Markovic and colleagues showed that PD patients with punding had cortical thinning of the right inferior frontal cortex, reduced functional connectivity between the habenula and frontal cortices, and enhanced functional connectivity of both the habenula and amygdala with the striatum and thalamus, compared with PD patients without ICBs and healthy controls, confirming the crucial role of the frontostriatal circuit in developing ICBs. Imperiale and colleagues showed that PD patients with ICBs had left precentral and superior frontal cortical thinning, together with motor and extramotor white‐matter tract damage. Moreover, the severity and duration of ICBs modulated the functional connectivity between sensorimotor, visual, and cognitive networks.…”
Section: Resultsmentioning
confidence: 99%